Perfil epidemiológico de salud bucal (conocimientos en salud bucal, índice de placa bacteriana, enfermedad periodontal, fluorosis y caries dental) en escolares matriculados en los grados de primero a tercero: colegio del Bosque Bilingüe año 2020 (2020)
Objective: Evaluate oral health condition (knowledge of oral health, bacterial plaque index, periodontal disease, fluorosis and dental caries) of children enrolled in first to third grade: Bilingual Forest School, Bogota, 2020. Materials and methods: Cross-sectional descriptive study to determine oral pathological entities present considering the following variables; gender, age, school grade, knowledge of oral health, bacterial plaque index, periodontal disease, fluorosis and caries dental. Previously to take the sample, it started to sign informed consents and approvals. Then it established the sample size of the current study. Before the beginning of the test, a space was prepared under the necessary conditions of each evaluator to allocate each one of themselves in space and time. Moreover, the sample was distributed in groups of five (5) participants organized by school grade. In the first stage, it applied knowledge of oral health and each participant was in an evaluation circuit. Following the process, it starts to apply bacterial plaque index, then the child went to the assigned zone to brush his or her teeth with evaluator control who was in charge to observe and advise how to do it with an adequate oral hygiene technique. After that, the child continued with a circuit where he or she was controlled by a second evaluator who took periodontal disease index (Rusell) and fluorosis dental index. At last, a third evaluator was in charge to check and register dental caries presence (ICDAS modified). Once gathered all samples under supervision and criteria union; it organized, proceed and registered information in an Excel file with the purpose of delete the major possible mistakes that can alter information veracity then create statistic charts to represent a reliable and scientific diagnosis. Outcomes: All children who were evaluated with the knowledge survey reported to have the habit of brushing their teeth, but they ignore the technique and the correct way of using the implements which was evidenced by the analysis and interpretation of the results of the bacterial plaque, (Sliness & Loe) where in the whole population without distinction of sex age or school degree presented accumulation of bacterial plaque, and it was registered and classified with high percentages in regular and deficient rates. In regard to the presence of periodontal disease, Russell’s community rate resulted in an average of 0.03454196, which determines that students do not have periodontal disease. The study of the prevalence of dental fluorosis showed that a large part of the students presented this pathology with a higher number of cases for males with a percentage of 67% between the ages of 7 and 8. In respect of dental caries results, it is possible to claim that it was most prevalent between the ages of 7 and 8 in female students at 43% Likewise, these results do not condition the presence of periodontal disease or dental caries at a high risk and percentage. Conclusions: the lack of technical knowledge and the proper use of the elements in oral hygiene were predisposing factors for the presence of bacterial plaque, and dental caries for that reason the approach on the population should be oriented to modify the predisposing factors of the disease.